Emma Barrandeguy: visible / invisible (Anclajes, 2018)
We propose a reading of the forms of configuration as author of the Argentine writer Emma Barrandeguy (1914-2006) in the history of national literature -and, within it, in the Lgbt/Queer literary tradition of Argentina-, focusing, on the one hand, on the canonizing processes of visibility / invisibility and, on the other hand, in certain writing and body’s policies that the author sustained both in her poetic, narrative and theatrical production as well as in her political militancy and in her ways of life.
Keywords: Emma Barrandeguy; Argentine Literature; Gender Studies; 20st Century; Argentina